Tinjauan Hukum Islam Terhadap Perkawinan Melalui Video Call - Wasilatul Fadilah (Tafhim Al-'Ilmi, 2022)
Abstract There is a difference of opinion among scholars regarding the law of marriage through video calls, namely according to the Hanafi madhhab it is valid while according to Syafi'iyah it is not valid. In the Hanafiyah school, one majlis is defined as the person who makes the contract can communicate directly and can carry out the contract at the same time. So any media can be used as long as it can connect the two parties without any manipulation. Meanwhile, according to Syafiiyyah, it is stated that one majlis is gathering in one place and time, marriage can be valid if all parties involved in the procession of the marriage contract must physically gather in one majlis. However, in fiqh law there is a solution for holding marriages remotely, namely through representatives or wakalah contracts either through letters, messengers, telephones, internet networks, video calls or the like. Keyword : Hukum Islam, Perkawinan, Video Call